Analisis Pola Persebaran Sekolah Menengah Atas (SMA) Menggunakan Sistem Informasi Geografis (SIG) di Kabupaten Deli Serdang - Irfan Ruhaimi; Novida Yenny (Geosfera: Jurnal Penelitian Geografi, 2025)
Deli Serdang Regency has the second largest population in North Sumatra with 2,048,480 inhabitants in 2024. It has a large area with diverse geographical characteristics (lowlands, hills and urban areas), which affects the distribution of senior high schools (SMA). This study aims to determine the distribution pattern of senior high schools (SMA) using a Geographic Information System (GIS) in Deli Serdang Regency. The method used is quantitative descriptive, with data analysis using Nearest Neighbour Analysis (NNA). The results show that the distribution pattern of senior high schools in Deli Serdang Regency is clustered with an NNA ratio of 0.621515, a Z-score of -8.628276, and a P-value of 0.000000, based on 142 school locations. This indicates that senior high schools in Deli Serdang Regency are not evenly distributed throughout the regency, but are clustered in certain areas and tend to be close to each other. The distribution pattern of senior high schools in Deli Serdang Regency is influenced by geographical conditions and regional characteristics, population, economic activity, and regional accessibility.